MEDICAL AND PSYCHOLOGICAL SUPPORT OF WOMEN WITH THE THREAT OF PRETERM BIRTH IN THE LAST TRIMESTER OF PREGNANCY AND AFTER DELIVERY - Н. Гринько; І. Герасим'юк; Б. Сумарюк (Bukovynian State Medical University, 2021)
Introduction. Throughout life, everyone faces a variety of emotionally complex situations. Pregnancy is one of such situations for a woman. It's a very strong level of experience and a specific set of sensations in life, the study of which has recently received close attention. Circumstances that have developed in Ukraine in connection with environmental disadvantages mainly determine the low health index of pregnant women, and create preconditions for the increasing frequency of premature pregnancies in future generations. This problem is of great medical and social importance. More than a third of babies born prematurely lag behind in physical and psychomotor development. Considering the above mentioned, it can be argued that the creation of a system of medical and psychological support for pregnant women with a risk of preterm birth in the last trimester of pregnancy is relevant, necessary and timely. The purpose of the study is to develop a set of measures for medical and psychological support of women at risk of preterm birth in the last trimester of pregnancy and after childbirth based on a systematic approach to the study of individual psychological, pathopsychological and psychosocial characteristics. Material and methods. During 2016-2019 the study was conducted based on Storozhynets Central District Hospital in the Chernivtsi region. 150 pregnant women in the third trimester of pregnancy (23-37 weeks) and their husbands were examined. The main group (MG) included 120 women with the risk of premature birth in the last trimester of pregnancy. The comparison group (CP) included 30 women with a physiological course of pregnancy. The main therapeutic group (MTG) consisted of 42 women with a risk of preterm birth in the last trimester of pregnancy with maladaptive (MTG1) and destructive (MTG2) types of interaction in the triad "mother-child-father", who agreed to participate in medical and psychological care. The correctional group (CG) included 12 women with a risk of preterm birth in the last trimester of pregnancy with maladaptive and destructive types of interaction in the triad "mother-child-father", who refused to participate in the proposed measures. Results. Analysis of the evaluation of the developed system of medical and psychological support of the family during pregnancy showed the following (p <0.001): a) improvement of psycho-emotional state, well-being and overcoming emotional stress demonstrated by MTG1 women (up to 43.7 ± 0.8 and 42.5 ± 1.5, respectively, and after 20.8 ± 1.5 and 22.1 ± 1.2, respectively), the level of depression and anxiety on the Hamilton scale (up to HDRS 11.4 ± 1.2 and HARS 12.5 ± 1.2 after HDRS 4.2 ± 0.4 and HARS 5.7 ± 0.4) and female MTG2 indicators of RA and PA on the Spielberger-Khanin scale (up to 51.7 ± 0.8 and 50.7 ± 1.5, respectively, and after 21.4 ± 1.8 and 23.1 ± 1.5, respectively), the level of depression and anxiety on the Hamilton scale (up to HDRS 16.3 ± 1.2 and HARS 18.3 ± 1.2 after HDRS 7.6 ± 0.7 and HARS 6.9 ± 0.6). Among CG women indicators RA and PA on the Spielberger-Khanin scale (up to 47.7 ± 0.8 and 46.6 ± 1.5, respectively; after 45.8 ± 1.5 and 42.1 ± 1.2, respectively), the level of depression and anxiety on the Hamilton scale (before HDRS 13.8 ± 1.2 and HARS 15.4 ± 1.2; after HDRS 12.2 ± 0.4 and HARS 14.7 ± 0.4) were higher. b) there was an increased level of social support on the last two scales - "support of colleagues" and "support of public organizations" among MTG1 and MTG2 women (up to 25.3%, after 55.2% / up to 14.8%, after 45, 2%, respectively) compared with CG women (up to 18.5%, after 24.5%). c)  there was a complete reduction of the deformation of marital relations in the majority of MTG1 (83.3%) and MTG2 (75%) women in contrast to the examined CG. Conclusions. The implementation of the system of medical and psychological support for women with a risk of preterm birth in the last trimester of pregnancy and after childbirth allowed to optimize the choice of adequate behavioral strategies in a family, improve emotional state and well-being, optimize women's attitudes to pregnancy and harmonize family interaction (72.5%) ˂0.001), to harmonize the relationship in the triad "mother - child - father" in the postpartum period (66.4%) (p˂0.001).